Does It Pay to be Good? The Performance of Indonesian Green Companies from 2009–2018 - Ega Annisa Rizti; Berly Martawardaya (Economics and Finance in Indonesia, 2022)
In Indonesia, KEHATI Sustainable and Responsible Investment (SRI) Index, hereafter referred to as SKI, aims to raise public awareness and help pro-environmental investors by selecting 25 highly rated public companies that adhere to the internationally accepted green business standard. This paper compared the financial performance of the companies listed in SKI and their counterparts between the period of January 2009 and December 2018 by predicting their future opening price of stock, comparing the performance of SKI to JKSE market index, and examining their financial performance using ROA and ROE as dependent variables. The findings suggest that being included in SKI is insignificant to the future opening price of stock. The index itself is found to be slightly more volatile than the market index, which is attributed by a previous study to SKI selection process lowering the chance for portfolio diversification and the volatility of the Indonesian market due to the financial crises. However, being included in the index positively affects both ROA and ROE, albeit small differences. Therefore, there is no significant difference between the financial performance of green companies in Indonesia and their counterparts.